Non-constancy of the bulk resistance of ionophore-based ion-selective electrode: A result of electrolyte co-extraction or of something else?. (1st January 2018) - Kondratyeva, Yevgeniya O.; Solovyeva, Elena V.; Khripoun, Galina A.; Mikhelson, Konstantin N.
Abstract: The bulk resistance of ionophore-based ion-selective electrodes (ISEs) is studied by means of chronopotentiometry and electrochemical impedance using Ca 2+ -ISEs with PVC membranes containing ETH 1001 as a model system. It is shown that the membrane bulk resistance is roughly the same within the range of CaCl2 concentrations from 0.3 to 10 −3  M, and increases significantly when the concentration is decreased to 10 −4 and 10 −5  M, although the potentiometric response of the ISEs is Nernstian in all these solutions. This increase of the resistance when 10 −3  M CaCl2 is further deleted is larger than the decrease of the resistance when CaCl2 is replaced with Ca(SCN)2 and Ca(ClO4 )2 . The results suggest that the non-constancy of the ISE bulk resistance is not caused by co-extraction of CaCl2 and therefore is not in conflict with the Nernstian behavior of the IESs potentials. The effect is tentatively ascribed to the regularities of water uptake by ISE membranes. Graphical abstract: Highlights: Bulk resistance of Ca 2+ -ISEs within the Nernstian response range is not constant. The resistance increases drastically when the solution concentration is below 10 −3  M. Most of the resistance change happens within a few minutes. The effect may be due to the regularities of water uptake by ISE membranes.